New possibilities for efficient laser surface treatment by diode‐pumped kW‐class lasers. Issue 13 (3rd August 2015) - Brajer, J.; Svabek, R.; Rostohar, D.; Divoky, M.; Lucianetti, A.; Mocek, T.; Madl, J.; Pitrmuc, Z.
Abstract : The newly developed so call multy‐slab laser at premise of the research centre HiLASE is already recognized as a potential new source for efficient laser surface treatments. Once the system is in full operation the pulses of up to 100J with pulse duration of 2‐10 ns will be delivered with repetition rate of 10 Hz. In this paper the status of this new laser system is presented. Additionally the design of a new experimental station for laser surface treatments is also discussed. According to preliminary plans the station will be ready for first experiments in 2016.